2018
DOI: 10.3892/etm.2018.5830
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide induces autophagy and apoptosis through ERK activation in human breast cancer MCF‑7 cells

Abstract: Abstract.To investigate the effects of triptolide (TPI) on proliferation, autophagy and death in human breast cancer MCF-7 cells, and to elucidate the associated molecular mechanisms, intracellular alterations were analyzed using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and flow cytometry assays. The results of the MTT assay revealed that TPI significantly reduced the MCF-7 cell survival rate when the concentration was >10 nmol/l. TPI activated a caspase cascade reaction by regulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 32 publications
5
17
0
Order By: Relevance
“…Although the mitochondria-mediated apoptotic induction by CDK inhibitors was shown in previous studies on prostate, breast, and colon cancer cells, the association of MAPK signaling in purvalanol-induced apoptosis was not clear. 22 In accordance with previous studies, we suggested that fine-tuning regulation of MAPKs in the CDK inhibitorinduced apoptosis mechanism is a promising target in the therapy of prostate cancer cells with high metastatic profile. 19 Knockeart et al 20 showed F I G U R E 5 MAPK inhibition further induced the CDK inhibitors-reduced cell survival axis and EMT related protein levels.…”
Section: Discussionsupporting
confidence: 89%
“…Although the mitochondria-mediated apoptotic induction by CDK inhibitors was shown in previous studies on prostate, breast, and colon cancer cells, the association of MAPK signaling in purvalanol-induced apoptosis was not clear. 22 In accordance with previous studies, we suggested that fine-tuning regulation of MAPKs in the CDK inhibitorinduced apoptosis mechanism is a promising target in the therapy of prostate cancer cells with high metastatic profile. 19 Knockeart et al 20 showed F I G U R E 5 MAPK inhibition further induced the CDK inhibitors-reduced cell survival axis and EMT related protein levels.…”
Section: Discussionsupporting
confidence: 89%
“…It induces mitochondrial apoptotic pathway to mediate apoptosis in Burkitt's lumphoma Raji, NAMALWA and Daudi cells, and inhibits tumor growth in Daudi xenograft mice [432], and inhibits cell proliferation through microRNA-181a up-regulation in human neuroblastoma SH-SY5Y cells [433]. Moreover, triptolide induces autophagy to induce apoptosis and inhibit angiogenesis in human osteosarcoma MG63 cells, and breast cancer MCF-7 cells [431,434]. In contrast, triptolide induces protective autophagy through calcium (Ca 2+ )/calmodulin-dependent protein kinase kinase β (CaMKKβ)-AMPK pathway in human prostate cancer PC-3, LNCaP and C4-2 cells, and through Akt/ mTOR down-regulation in human cervical SiHa cells [420,435].…”
Section: Triptolidementioning
confidence: 99%
“…Moreover, ERK is also shown to be important in mediating triptolide-induced anti-cancer activities. Triptolide induces apoptosis through ERK activation in human breast cancer MDA-MB-231 and MCF-7 cells [434,442], and ERK activation leads to caspase activation, Bax up-regulation and Bcl-xL down-regulation [442]. On the other hand, it can also inhibit metastasis through ERK down-regulation in esophageal squamous cell cancer KYSE180 and KYSE150 cells, and murine melanoma B16F10 cells [443,444].…”
Section: Triptolidementioning
confidence: 99%
“…More recently, studies by Liu and coworkers [32] demonstrated that knockdown of CAV-1 in A549 cells enhanced cisplatin-triggered cancer death. Because of the growth inhibition and associated apoptotic effects of TL in a wide variety of epithelial and hematological cancer cell lines [5][6][7][8][9][10][11], including NSCLC cells [4,12], we investigated the potential changes in CAV-1 mRNA/ protein expression following TL treatment in A549 and NCI-H460 lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%